The Effect of Tax Planning, Deferred Tax Expense, and Audit Quality on Earnings Management in Property and Real Estate Sub-Sector Companies - Zogara, Ita Diana; Pradnyani, Ni Luh Putu Sri Purnama; Artaningrum, Rai Gina (Pertapsi-Indonesia collaborated with Petra Christian University, 2025)
Profit management is a condition where management intervenes in the process of preparing financial statements for external parties so that the amount of profit can be leveled, increased, and decreased. Profit is the simplest measure to assess company performance. Information about profit has a significant role for parties with an interest in a company. The goal that management wants to achieve is to make high profits. This is directly related to the bonus that the management will receive, as the higher the profit earned, the higher the bonus that the company will give to the management as a direct manager. The research method used is the quantitative research method with secondary data. This research was conducted at property and real estate subsector companies listed on the Indonesia Stock Exchange in 2020-2023. The method of determining the sample is purposive sampling. Multiple linear regression analysis is the data analysis technique used. The results of this study indicate that tax planning has a positive effect on profit management, deferred tax expense has a positive effect on profit management, and audit quality has a negative effect on profit management. According to these findings, there are three factors that affect profit management: tax planning, deferred tax expense, and audit quality. The above factors can be taken into consideration by company management in developing the company and become a benchmark for investors in making decisions to invest.